Geographical patterns of Fejervarya limnocharis gut microbiota by latitude along mainland China’s coastline - Zhao, Na; Ma, Zhiwei; Jiang, Yixin; Shi, Yingying; Xie, Yuning; Wang, Yuting; Wu, Siyu; Liu, Shelan; Wang, Supen (Frontiers in Microbiology, 2022)
Abstract The gut microbiota affects many aspects of host biology and plays key roles in the coevolutionary association with its host. Geographical gradients may play a certain role on gut microbiota variation in the natural environment. However, the distribution pattern of amphibian gut microbiota in the latitudinal gradient remains largely unexplored. Here, we sampled six natural populations of Fejervarya limnocharis along the eastern coastline of mainland China (spanning 20°- 30° N = 1300 km) using 16S rRNA amplicon sequencing to characterize the gut microbiota. First of all, a significant correlation between gut microbial diversity and latitude was observed in our research system. Second, we discovered that latitude influenced the composition of the gut microbiota of F. limnocharis. Finally, we detected that geographical distance could not determine gut microbiota composition in F. limnocharis. These results indicate that latitude can play an important role in shaping the gut microbial diversity of amphibian. Our study offers the first evidence that gut microbial diversity of amphibian presents a latitudinal pattern and highlights the need for increased numbers of individuals to be sampled during microbiome studies in wild populations along environmental gradients.